Apakah Pariwisata Mempengaruhi Ketimpangan? Bukti dari Daerah Istimewa Yogyakarta - Dzaky, Muhammad; Nugroho, Akbar Bagus (Gadjah Mada Journal of Tourism Studies, 2024)
It was initially believed that tourism was a sector capable of reducing global inequality in numerous academic and practical discussions. Nevertheless, in the years that followed, a number of academics and scholars began to question the efficacy of tourism as a means of reducing regional inequality. Therefore, the objective of this study is to determine whether tourism has the potential to alleviate or exacerbate inequality in a given region. The Yogyakarta Special Region Province serves as the focal point of this study. This study employs secondary data that is publicly accessible through the DIY Tourism Statistics page and the National Planning Agency (Bappenas). Income inequality, as denoted by the GINI index, serves as the dependent variable in this inquiry. The GINI index is a numerical value between 0 and 1, with 0 indicating an equal income distribution and 1 indicating ideal income inequality. The independent variable in this study is government revenue from the tourism sector (PP). This research indicates that the income of the tourism industry to the DIY government exacerbates the income distribution in DIY, particularly in the GINI index corridor.